Diagnostic Accuracy and Safety of Endoscopic – Guided Office-Based Biopsies for Laryngeal and Pharyngeal Lesions at St. Luke’s Medical Center - Diana Fernandez; Ronaldo Soriano (Philippine Journal of Otolaryngology Head and Neck Surgery)
Objective: To determine the sensitivity, specificity, positive predictive value, negative predictive value and safety of endoscopic guided office-based biopsies (OBB) in diagnosing laryngeal and pharyngeal neoplasms at the St. Luke’s Medical Center in Quezon City and Global City.